Childhood muscular fitness phenotypes and adult metabolic syndrome. - Fraser, B; Huynh, Q; Schmidt, M; Dwyer, T; Venn, A; Magnussen, C (American College of Sports Medicine, 2016)
Introduction To determine whether childhood muscular fitness phenotypes (strength, endurance, power) are independently associated with adult metabolic syndrome (MetS). Methods Longitudinal study including 737 participants who had muscular fitness measures in 1985 when aged 9, 12, or 15 years and attended follow-up in young adulthood 20 years later when measures of MetS were collected. Childhood measures of muscular fitness included strength (right and left grip, leg, shoulder extension and flexion), endurance (number of push-ups in thirty seconds), and power (distance of a standing long jump). A muscular fitness score was created using all individual muscular fitness phenotypes. In adulthood, waist circumference, blood pressure, high-density lipoprotein cholesterol, triglycerides, and glucose were measured. Adult outcomes were MetS defined using the Harmonized definition and a continuous metabolic syndrome (cMetS) risk score. Results Participants with childhood muscular strength, muscular power and combined muscular fitness score in the highest third had significantly lower relative risk (RR) for MetS and a lower cMetS score in adulthood independent of cardiorespiratory fitness (CRF), than those in the lowest third (strength: RR=0.39 (0.19,0.78); β=-0.39 (-0.52, -0.25), power: RR=0.32 (0.15,0.68); β=-0.39 (-0.53, -0.26), fitness score: RR=0.30 (0.14,0.63); β=-0.45 (-0.58, -0.31)). However, adjustment for childhood waist circumference reduced the effect sizes for both adult outcomes by 44-51%. Conclusion Phenotypes of childhood muscular fitness predict adult MetS independent of CRF. Although approximately half of the effect of childhood muscular fitness on adult MetS is potentially being mediated by child waist circumference, these data suggest promotion of muscular fitness among children might provide additional protection against developing adult MetS.